Perceptions of final-year medical students and interns toward pursuing a career in critical care medicine - Ageel, Mohammed (Frontiers in Medicine, 2025)
BackgroundCritical care medicine (CCM) faces challenges in attracting new physicians due to its demanding nature. Understanding medical students’ and interns’ perceptions of CCM is essential to address physician shortages and improve medical training.ObjectiveTo evaluate the factors influencing specialty selection and explore perceptions of final-year medical students and interns toward CCM at Jazan University.MethodsA cross-sectional survey using convenience sampling was conducted. Participants completed questionnaire assessing factors influencing career choice and perceptions of CCM. Chi-squared tests analyzed the associations between demographic variables and perceptions.ResultsThe study included 165 medical students (80% interns, 20% final-year students), primarily male (56.36%) and single (90.91%), with a mean age of 24.56 ± 1.46 years. The most influential career factors were job security (11.65%), enthusiasm/commitment (10.36%), and acceptable working hours (10.36%). Most students (81.82%) found CCM intellectually challenging, while 76.36% recognized its financial benefits. However, only 29.09% were considering a career in CCM, with concerns about work-life balance (34.54%) and family time (32.73%). Interns were more likely than final-year students to view limited working hours positively (p = 0.046), perceive greater colleague prestige (p = 0.035), expect private practice opportunities (p = 0.004), anticipate higher salaries (p < 0.001), and acknowledge the shortage of staff in CCM (p = 0.009).ConclusionThere is a tension between the intellectual and financial benefits of CCM and its lifestyle demands. While students recognize its rewards, concerns about work-life balance and staffing challenges discourage many from pursuing the specialty. Tailored career counseling, mentorship, and addressing lifestyle concerns in medical curricula may improve interest in CCM.